Synthetic Sugar Substitutes Alter Intestinal Epithelial Cell Proliferation and Differentiation in a Cell-Line Dependent Manner In Vitro. (14th June 2022) - Richardson, Irene; Heflin, Kelsey; Hunt, Bryce; Lee, Joseph; Frese, Steven
Abstract: Objectives: The acute and long-term effects of synthetic sugar substitutes have yet to be fully determined. Importantly, their interactions with the gut epithelium are poorly understood. The objective of this study was to examine the impact of two synthetic sugar substitutes on intestinal epithelial cells in terms of 1) cellular toxicity, 2) effects on cell proliferation, and 3) effects on cellular differentiation. Methods: Gut epithelial cells (n = 3/group) were challenged for 3 hours with varying concentrations of saccharin and sucralose, to determine cellular toxicity thresholds, as assessed by MTT assay. Three morphologically distinct epithelial cell lines (HT-29, HT-29MTX, and T84) were also challenged (n = 3/group) with the maximum concentrations of these compounds that did not induce toxicity to evaluate cell proliferation over a 96-hour period. RNA was isolated from synthetic sugar substitute-challenged cells and analyzed for epithelial cell differentiation-related gene expression via CDX2 by qRT-PCR, and normalized to B2M, an epithelial cell reference gene. Results: Cellular toxicity assays indicated that 10% w/v sweetener was the maximum level tested that avoided evidence of cellular toxicity. When comparing distinct epithelial cell lines, HT-29MTX and T84 displayed significant differences in cell proliferation when exposed to saccharin (HT29-MTX, P < 0.01) and sucralose (T84, P < 0.01), demonstrating increased cell proliferation, relative to unchallenged controls. Finally, CDX2 expression, a marker of cellular differentiation, was significantly increased in the presence of both saccharin (5% w/v) and sucralose (10% w/v) in HT-29 cells, relative to unchallenged controls (P < 0.05). Conclusions: These findings demonstrate that exposure to high concentrations of synthetic sugar substitutes alter proliferation and differentiation of gut epithelial cell lines in vitro, in a cell line-dependent manner. Additional research is necessary to determine whether these interactions also occur in vivo . Funding Sources: This work was funded by the University of Nevada, Reno Department of Nutrition, the College of Agriculture, Biotechnology, & Natural Resources, the Vice President for Research and Innovation, and the Nevada Agricultural Experiment Station.